Catharsis as a condition for building youth resilience during war - Sodolevska Валерія (Psychosomatic Medicine and General Practice, 2023)
This manuscript is the abstract of the VI Scientific and Practical Conference with International Participation "Psychosomatic Medicine: Science and Practice", held on November 2-3, 2023 in Kyiv on the Mediamed platform.